Shakespeare's History Plays Rethinking Historicism - Parvini, Neema (Edinburgh University Press, 2012)
Shakespeare's History Plays boldly moves criticism of Shakespeare's history plays beyond anti-humanist theoretical approaches.This important intervention in the critical and theoretical discourse of Shakespeare studies summarises, evaluates and ultimately calls time on the mode of criticism that has prevailed in Shakespeare studies over the past thirty years. It heralds a new, more dynamic way of reading Shakespeare as a supremely intelligent and creative political thinker, whose history plays address and illuminate the very questions with which cultural historicists have been so preoccupied since the 1980s. In providing bold and original readings of the first and second tetralogies ( Henry VI, Richard III, Richard II and Henry IV, Parts 1 & 2), the book reignites old debates and re-energises recent bids to humanise Shakespeare and to restore agency to the individual in the critical readings of his plays.